Big Banks, Idiosyncratic Volatility, and Systemic Risk - Fernholz, Ricardo T.; Koch, Christoffer (American Economic Review, 2017)
Starting in the 1990s, US bank assets grew more concentrated among a few large institutions. We explore the changing role of idiosyncratic volatility as a shaping force of the bank asset power law distribution. Our results reveal that idiosyncratic asset volatilities for bank-holding companies declined since the 1990s. To the extent that firm-specific shocks can have significant macroeconomic consequences, this result implies that even as one obvious source of aggregate risk and contagion–bank asset concentration–has increased, another important source–idiosyncratic volatility–has diminished.